Magnitude and significance of interarm blood pressure differences in children and adolescents. Issue 7 (July 2021) - Clarke, Melanie M.; Harrington, Hilary A.; Glenning, Jonathan P.; Zannino, Diana; Holmstrup, Michael E.; Jensen, Brock T.; Smolich, Joseph J.; Cheung, Michael M.H.; Mynard, Jonathan P.
Abstract : Background: An interarm difference (IAD) in blood pressure (BP) of 10 mmHg or more is a potential cardiovascular risk factor in adults, given its association with cardiovascular events/mortality. In children and adolescents, accurate BP assessment is critical for identifying risk of end organ damage. However, IAD has not been systematically studied in paediatric patients; if present and of significant magnitude, measuring BP in only one arm could lead to misclassification of hypertensive status. Method: In 95 children/adolescents with a normal aorta (including 15 with a history of tetralogy of Fallot) aged 7–18 years attending the Royal Children's Hospital, Melbourne, we aimed to determine the magnitude of IAD, frequency of IAD of at least 10 mmHg, difference in BP classification between arms, and influence of repeat measures on IAD in a single visit. After 5 min rest, simultaneous bilateral BP was measured in triplicate with an automated device. Results: Absolute systolic IAD was 5.0 mmHg (median, interquartile range 2–8 mmHg) and was 10 mmHg or more in 14%, with no change on repeat measures. In patients with a history of aortic surgery, IAD of 10 mmHg or more occurred in 27% (transposition of the great arteries, n  = 15) and 75% (aortic coarctation, n  = 8). Differences in BP classification, based on initial left vs. right arm measures, occurred in 25% (normal aorta) and 40%/63% (aortic surgery), or 17% and 33%/50%, respectively if second and third measurements were averaged. Conclusion: Substantial interarm BP differences were common, even in apparently healthy children and adolescents: evaluation of IAD may, therefore, be important for BP classification in the paediatric setting.